Clinical presentation, diagnostic findings, and outcome of adult horses with equine coronavirus infection at a veterinary teaching hospital: 33 cases (2012–2018). (June 2019) - Berryhill, E.H.; Magdesia, K.G.; Aleman, M.; Pusterla, N.
Highlights: Equine coronavirus (ECoV) is a differential diagnosis for adult horses with fever, mild colic signs, and anorexia. Leukopenia tends to be more severe in ECoV-infected horses than uninfected horses with similar signs. Horses shedding ECoV should be evaluated for co-infections. ECoV-infected horses may require intensive care to treat systemic inflammation, dehydration, and electrolyte derangements. Abstract: Equine coronavirus (ECoV) is a recently described enteric virus with worldwide outbreaks; however, there are little data available on clinical presentation, diagnosis, and outcome. The study objective was to document case management of ECoV in adult horses presented to a referral hospital and compare to a cohort of horses that tested negative for ECoV. A retrospective case series was performed based on positive real-time quantitative PCR results for ECoV on faeces from horses treated at the UC Davis Veterinary Medical Teaching Hospital from 1 March 2012 to 31 March 2018. Horses negative for ECoV were matched to the ECoV-positive group as controls. Data collected included signalment, history, exam findings, diagnostics, treatment, and follow-up. Thirty-three horses (median age, 11 years; range, 2–37 years) tested ECoV-positive, including three horses with co-infections. Presenting complaints for ECoV-infected horses included historic fevers ( n  = 25/30; 83%), anorexia ( n  = 14/30; 47%), and colic ( n  = 13/30; 43%). ECoV-positive horses had significantly lower white blood cell (median, 3.0 × 10 9 /L; range, 0.68–16.2 × 10 9 /L), neutrophil (median, 1.26 × 10 9 /L; range, 0.15–14.4 × 10 9 /L), and lymphocyte (median, 0.86 × 10 9 /L; range, 0.42–3.47 × 10 9 /L) counts than ECoV-negative horses. Electrolyte and metabolic derangements and scant faeces were common. Twenty-seven horses were hospitalised for a median of 5 days (range, 0.5–14 days), with 26/27 (96%) horses surviving to discharge. ECoV infection should be a differential diagnosis for adult horses with fever, colic, anorexia, and leukopenia. The disease has a low mortality rate, but horses may require intensive care to resolve severe leukopenia, systemic inflammation, and metabolic disturbances.